2004
DOI: 10.1590/s0103-65132004000100005
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de fornecedores: um estudo de caso utilizando a troca rápida de ferramentas

Abstract: Due to the increasing concurrence among companies, looking for production advantages is of paramount importance, mainly if the benefits are such that they can be extended to all levels of the supply chain. The aim of this paper is to present a program for suppliers development. The program was designed by an automotive company facing the need of increasing the overall capacity of its suppliers, helping them to achieve improvements in operations and processes. The actions conducted in one of the suppliers, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In their study they analyzed more than 60 cases and concluded that up to 90 % of setup times could be improved. Neumann and Ribeiro (2004) analyzed how a supplier development program achieved a 50 % of improvement in the set up time of the firm. Sugai, McIntosh and Novaski (2007), addressing a single case study, concluded that the sequencing of production lots, the acceleration (during the setup) and deceleration (during post-setup) periods and the need to maintain rigorous set up times achieved are very important topics.…”
Section: Single-minute Exchange Of Diementioning
confidence: 99%
“…In their study they analyzed more than 60 cases and concluded that up to 90 % of setup times could be improved. Neumann and Ribeiro (2004) analyzed how a supplier development program achieved a 50 % of improvement in the set up time of the firm. Sugai, McIntosh and Novaski (2007), addressing a single case study, concluded that the sequencing of production lots, the acceleration (during the setup) and deceleration (during post-setup) periods and the need to maintain rigorous set up times achieved are very important topics.…”
Section: Single-minute Exchange Of Diementioning
confidence: 99%
“…There are numerous perceived benefits to the supplier evaluation system. Among those: (1) meet the suppliers in more detail, (2) correct procedures and practices that can help suppliers to obtain better performance, (3) based on a diagnosis, more specialized, forward future actions for the benefit of the best suppliers, (4) improve the supplier's opinion about their practices, previously grounded only in reducing cost, and (5) achieve improvements in different areas, including increase competitiveness and extend gains for the entire organization (Neumann & Ribeiro, 2004).…”
Section: Supplier-evaluation Systemmentioning
confidence: 99%
“…The techniques for reducing the changeover time enable the economical production of small lots, resulting in more flexibility to respond to market changes (Lozano et al, 2019;Bidarra et al, 2018;Braglia et al, 2017;Chaves et al, 2015;Yu, 2012;Conceicao et al, 2009). The shorter equipment changeover time, the smaller the production lot can be, resulting in higher production effectiveness (Silva and Godinho Filho, 2019;Antunes et al, 2013;Cakmakci, 2009;Neumann and Ribeiro, 2004). Reductions in setup time can be attained via SMED when the equipment changeover time is reduced (Mihok et al, 2015).…”
Section: Introductionmentioning
confidence: 99%